2020
DOI: 10.9734/jeai/2020/v42i230478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bread Waste Fortified with Moringa Leaf Meal on Performance and Health Status of Broiler Chickens

Abstract: Aim: This study is to evaluate the effects of using bread waste fortified with moringa leaf meal on broiler chickens. Methodology: Bread wastes were sun-dried and moringa leaves air-dried. The two dried products were milled separately. Thereafter, the meals were mixed in ratio 9:1 (9 kg Bread Waste + 1 kg Moringa Leaf) to produced fortified bread wastes. Four broiler starter diets and four finisher diets were formulated using fortified bread waste at graded levels of 0, 5, 10 and 15% and designated diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…From a study conducted by Adegbenro et al (2017), five (5) tropical vegetables were mixed in ratio 1:1:1:1:1 into a composite meal and used to replace broiler commercial premix at 0. 1.…”
Section: Tropical Vegetables In Poultry Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a study conducted by Adegbenro et al (2017), five (5) tropical vegetables were mixed in ratio 1:1:1:1:1 into a composite meal and used to replace broiler commercial premix at 0. 1.…”
Section: Tropical Vegetables In Poultry Nutritionmentioning
confidence: 99%
“…Also, there was a trend towards a reduction in the cholesterol level as the inclusion level of composite meal in the diets was increased. Adegbenro et al (2017) also reported reduction in values for the belly fat as the level of composite leaf meal produced from the five (5) tropical vegetables inclusion increased, thus indicating the potential of the leaf meals to reduction of fat deposition in the muscle and therefore could help in the prevention and reduction of neurodegenerative diseases associated with lipid-rich diets (Upadhyay, 1990;Oforjindu, 2006).The complete replacements of commercial premix with composite leaf meal at 5% inclusion level led to ₦4.00 reduction. This translates to a colossal savings of ₦40,000 for the diet per tonne by farmers.…”
Section: Tropical Vegetables In Poultry Nutritionmentioning
confidence: 99%
“…Rabbit are generally prolific, early maturing, fast growth and have short generation interval. All these attributes make rabbit an ideal animal for meat production, especially among developing countries in the tropics such as Nigeria where shortage of animal protein intake among the populace is usually a common problem [2,3,4,5]. On the other hand, rabbit plays a vital role in the utilization of fibrous by-products which can be converted into animal protein for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…(Kim et al, 2012). The advance in the poultry industry in developing countries has led to an increase in the demand for feed and feed ingredients which is the major constituent in poultry production (Adegbenro, 2016, Adegbenro et al, 2020. It has gradually been established that the supplies for conventional feed ingredients cannot be met, even according to optimistic forecasts (Yenesew et al, 2015).…”
Section: Introductionmentioning
confidence: 99%